RUBELLA - SHOULD IT BE A PRIORITY IN THE NATIONAL IMMUNIZATION PROGRAMMES? - Wazir, Muhammad Salim; Iqbal, Shahid (Journal of Ayub Medical College Abbottabad, 2015)
Rubella is a mild infection of childhood and young adults with 75% of cases occurring in age group 15-45 years. In unvaccinated populations, rubella usually occurs in spring with epidemics in 6-9 years cycles. Rubella has devastating effects on growing foetus if contracted by women in the first trimester of pregnancy. Perinatal infection of Rubella contributes to 2-3% of all congenital anomalies. Over the past three decades many resource risk countries have introduced universal or selective immunization programs against rubella with evidence that such interventions reduce the incidence of congenital rubella syndrome. In Pakistan the schedules of the Expanded Program on Immunization (EPI) do not include immunization against rubella and evidence is needed to estimate the risk of congenital rubella with a view to start immunization programmes to combat the menace of Congenital Rubella Syndrome (CRS). Logistically it is easy to add rubella vaccine to the already existing EPI schedules as measles is given on 9th and 15 month with little implications for cost, resulting in great reduction in CRS.